2014
DOI: 10.1111/josi.12083
|View full text |Cite
|
Sign up to set email alerts
|

Allies against Sexism: The Role of Men in Confronting Sexism

Abstract: Consider recent actions by two politicians. The first campaigned for women to have equal representation in the government and pursued equal pay for women in the workplace. The second made campaign promises to reduce the gender gap in pay and used the first bill signing as a new leader to enact a law making it easier for women to recoup wages lost as a result of sexism. These politicians share something in common; they are both men (the first is French President Francois Hollande and the second is U.S. Presiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
209
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(225 citation statements)
references
References 58 publications
4
209
0
1
Order By: Relevance
“…Although targets (e.g., Blacks, women) and nontargets (e.g., Whites, men) both decrease stereotyping through confrontation (Czopp et al., ), previous research is mixed on the effect of target or nontarget confrontation on other outcomes (Blanchard et al., ; Czopp & Monteith, ). Our finding that a man's (vs. woman's) confrontation was more surprising replicates Czopp and Monteith's () finding that nontarget (vs. target) confronting is unexpected (Drury & Kaiser, ). However, Study 2 found no difference in perceptions of sexism based on whether the confronter was a target (i.e., woman) or nontarget (i.e., man) of sexism.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although targets (e.g., Blacks, women) and nontargets (e.g., Whites, men) both decrease stereotyping through confrontation (Czopp et al., ), previous research is mixed on the effect of target or nontarget confrontation on other outcomes (Blanchard et al., ; Czopp & Monteith, ). Our finding that a man's (vs. woman's) confrontation was more surprising replicates Czopp and Monteith's () finding that nontarget (vs. target) confronting is unexpected (Drury & Kaiser, ). However, Study 2 found no difference in perceptions of sexism based on whether the confronter was a target (i.e., woman) or nontarget (i.e., man) of sexism.…”
Section: Discussionsupporting
confidence: 87%
“…Study 2 further revealed that public confrontations increased sexism perceptions of gender bias. Applied to workplace settings, this pattern of results suggests that publically confronting everyday prejudice, including gender bias (De Lemus, Navarro, Megías, Velásquez, & Ryan, ) or sexual harassment (Buchanan & Settles, ; Drury & Kaiser, ), causes people to see these actions as more sexist. Thus, organizations should lead by example and encourage people to publically confront.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ragins et al (2007) found that the best predictor of fear of disclosure (the fear of fully disclosing one's sexual orientation at work) was the perceived presence of supportive supervisors and co-workers. Research on confronting prejudice suggests that the most effective confronter is a member of the nontarget group (i.e., a European-American confronting an example of prejudice against an African-American; Gulker, Mark, & Monteith, 2013;Rasinski, & Czopp, 2010;Stangor, Sechrist, & Jost, 2001; a male confronting sexism, Drury & Kaiser, 2014;Gervais & Hillard, 2014). Brooks and Edwards (2009) discussed the importance of having an ally-a person from the majority group who advocates support and equal rights for members of minority groups.…”
Section: Applied Implicationsmentioning
confidence: 99%
“…These findings also held true when the remark was racist rather than sexist and regardless of individual differences in participant prejudice. Moreover, patterns of results were consistent even when removing individuals who did not share group membership with the target of the prejudicial remark, which is important given increasing evidence for the effectiveness of ally confronters (e.g., Drury & Kaiser, ) and given that discriminatory remarks are often made in the absence of people directly targeted by the remarks. Together, the findings highlight the robust impact of perpetrator power on confrontation intentions.…”
Section: Discussionmentioning
confidence: 78%